Psychosocial factors as longitudinal predictors of bulimic symptomatology among female collegiate athletes. (September 2016) - Voelker, Dana K.; Petrie, Trent A.; Neumann, Craig S.; Anderson, Carlin M.
Abstract: Objectives: This study examined the within-variable stability and prospective cross-lagged pathways between body satisfaction, negative affect, self-reported intentions to engage in dietary restraint, and bulimic symptomatology among female collegiate athletes in weight-sensitive sports. Design: This study employed a cross-lagged longitudinal design. Method: Female collegiate gymnasts, swimmers, and divers ( n  = 325) completed paper-pencil survey batteries at the beginning (Time 1) and end (Time 2) of their 5-month athletic season, including measures of body satisfaction, intentions to engage in dietary restraint, negative affect, and bulimic symptomatology. Results: From Time 1 to Time 2, stability coefficients were highest for intentions to engage in dietary restraint and bulimic symptomatology. Significant cross-lagged relations revealed that Time 1 body satisfaction predicted a decrease in Time 2 negative affect, Time 1 bulimic symptomatology predicted a decrease in Time 2 body satisfaction, and Time 1 negative affect predicted a decrease in Time 2 intentions to engage in dietary restraint. Conclusions: The relative stability of intentions to engage in dietary restraint and bulimic symptomatology suggests that certain disordered eating behaviors may become more resistant to change over the course of an athletic season and solidify while competing in college. The cross-lagged associations demonstrate the importance of targeting body satisfaction, negative affect, and bulimic behaviors when designing interventions for female collegiate athletes, and implementing such programs at the beginning of an athletic season. Risk factors for bulimic symptomatology should be examined over a time period longer than one athletic season and during transitional experiences (e.g., high school to college sports). Highlights: Time 1 body satisfaction predicted decreased Time 2 negative affect. Time 1 bulimic symptomatology predicted decreased Time 2 body satisfaction. Time 1 negative affect predicted decreased Time 2 dietary restraint. Longitudinal eating disorder research is critical to targeted interventions in sport.